The Crossroads of Glycoscience, Infection, and Immunology - McKitrick, Tanya R.; Ackerman, Margaret E.; Anthony, Robert M.; Bennett, Clay S.; Demetriou, Michael; Hudalla, Gregory A.; Ribbeck, Katharina; Ruhl, Stefan; Woo, Christina M.; Yang, Loretta; Zost, Seth J.; Schnaar, Ronald L.; et al. (Frontiers in Microbiology, 2021)
Advances in experimental capabilities in the glycosciences offer expanding opportunities for discovery in the broad areas of immunology and microbiology. These two disciplines overlap when microbial infection stimulates host immune responses and glycan structures are central in the processes that occur during all such encounters. Microbial glycans mediate host-pathogen interactions by acting as surface receptors or ligands, functioning as virulence factors, impeding host immune responses, or playing other roles in the struggle between host and microbe. In the context of the host, glycosylation drives cell-cell interactions that initiate and regulate the host response and modulates the effects of antibodies and soluble immune mediators. This Perspective reports on a workshop organized jointly by the National Institute of Allergy and Infectious Diseases and the National Institute of Dental and Craniofacial Research in May, 2020. The conference addressed the use of emerging glycoscience tools and resources to advance investigation of glycans and their roles in microbe-host interactions, immune mediated diseases, and immune cell recognition and function. Future discoveries in these areas will increase fundamental scientific understanding and have the potential to improve diagnosis and treatment of infections and immune dysregulation.